The cloud is not 'there', we are the cloud!. (1st January 2013) - Mousannif, Hajar; Khalil, Ismail; Kotsis, Gabriele
Cloud computing has emerged as one of the most highly discussed topics both in the academic community and in the computing industry. Many big computer industry players such as Microsoft, IBM and Sun, as well as other Internet technology heavyweights, including Google and Amazon, have a long time ago started delivering standardised services in a self-service and pay-peruse way. However, why pay when you can simply cooperate? This paper takes the first exploratory step in this direction by introducing a new Peer-to-Peer cloud architecture we refer to as Cooperation as a Service (CaaS) that allows providing cloud participants with a whole set of Infrastructure, Platform and Software cloud services for free by taking advantage of cooperation among different peers.